2012
DOI: 10.1103/physrevb.85.195136
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-enhanced coherence between two-dimensional Dirac layers

Abstract: We estimate the strength of interaction-enhanced coherence between two graphene or topological insulator surface-state layers by solving imaginary-axis gap equations in the random phase approximation. Using a self-consistent treatment of dynamic screening of Coulomb interactions in the gapped phase, we show that the excitonic gap can reach values on the order of the Fermi energy at strong interactions. The gap is discontinuous as a function of interlayer separation and effective fine structure constant, reveal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 44 publications
2
115
1
Order By: Relevance
“…In QCD with gauge group SU(2) there is a so-called quarkyonic regime above onset where ∝ μ 2 [16]; this is consistent with degenerate fermions in 3 + 1d with a gap ∼ O( QCD ) independent of μ. It is also very different from the result /μ ∼ O(10 −7 ) obtained by self-consistent diagrammatic techniques [7], although comparable with the large values of /μ obtained in [5], where it was found that depends sensitively on the treatment of screening effects, and in particular on the reduction of screening once the superfluid gap forms. One feature of our approach which does merit comparison with the treatment in [5] is that competition between inter-and intralayer pairing condensates can be addressed; see Fig.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…In QCD with gauge group SU(2) there is a so-called quarkyonic regime above onset where ∝ μ 2 [16]; this is consistent with degenerate fermions in 3 + 1d with a gap ∼ O( QCD ) independent of μ. It is also very different from the result /μ ∼ O(10 −7 ) obtained by self-consistent diagrammatic techniques [7], although comparable with the large values of /μ obtained in [5], where it was found that depends sensitively on the treatment of screening effects, and in particular on the reduction of screening once the superfluid gap forms. One feature of our approach which does merit comparison with the treatment in [5] is that competition between inter-and intralayer pairing condensates can be addressed; see Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…Although V defined in this way yields a potential with no classical Coulomb r −1 tail, it was shown in [6] that V and A 0 in (1) have the same large-N f quantum corrections, and the models coincide in the strong coupling limit e 2 ,g 2 → ∞. Because some weak interlayer hybridization is likely to be present in double-layer systems, in general j = 0 [5]; however we will attempt to extrapolate j → 0 so that exciton condensation can be viewed as a spontaneous symmetry breaking U (4) ⊗ U (4) → U (4) [1]. In continuum notation the covariant derivative operator including the bias voltage is…”
Section: Formulation and Simulation Of The Modelmentioning
confidence: 99%
See 3 more Smart Citations